Thermal annealing effects on vanadium pentoxide xerogel films - Barbosa, Glauciane do Nascimento; Graeff, Carlos Frederico de Oliveira; Oliveira, Herenilton Paulino (Eclética Química, 2005)
The effect of water molecules on the conductivity and electrochemical properties of vanadium pentoxide xerogel was studied in connection with changes of morphology upon thermal annealing at different temperatures. It was demonstrated that the conductivity was increased for the samples heated at 150 o C and 270 o C compared to the vanadium pentoxide xerogel. It was also verified a stabilization of electrochemical processes of the insertion and de-insertion of lithium ions the structure of thermally annealed vanadium pentoxide.